Baobab Tree at Jijamata Udyan - Ghosh, Ayan (2023)
Among the notable exotic plants at Jijamata Udyan are Baobab trees, which are native to Madagascar, parts of mainland Africa, and Australia. The tree was brought to India by Abyssinian traders more than 1,000 years back. Its bark fibre is used for making ropes and its fruit is relished by monkeys, hence also known as the 'Monkey Bread Tree'.